Sistem Informasi Tunjangan Kinerja Untuk Menentukan Tambahan Penghasilan Pegawai Negeri Sipil Menggunakan Metode Design Science Research - Reza Andrian (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Providing Additional Employee Income (TPP) is a refinement of existing benefits and will bea specific allowance to boost performance and at the same time guarantee fairness in theprovision of benefits. Lately, there has been a decline in the percentage of service quality levelsto the community and staffing administration services. This is due to the slow acceptance ofTPP to the employees, causing disciplinary and demotivation to the employees. Not only that,there are many other factors that influence this delay, especially concerning the incompletesupporting documents, errors in calculations and the absence of regulations regarding theimplementation of performance allowances in each agency. Therefore, to help solve existingproblems, an information system design is needed that can help to make it easier to determineTPP by using the Design Science Research method. From the results of testing the TechnologyAcceptance Model (TAM) hypothesis states that the system that has been made is acceptableand the influence of user convenience, usability and attitude variables has an influence of92.5% and from the results of testing the success of the system using the DeLone and McLeanmodel 9 hypotheses submitted 7 hypotheses proven significantly, the test results prove thatService Quality does not have a positive effect on User Satisfaction and User Satisfaction doesnot have a positive effect on the System Benefit (Net Benefit) while other variables are testedsignificant in measuring the success of users system, so the model is stated to be appropriatein representing the results of the study